2009
DOI: 10.1002/chem.200901548
|View full text |Cite
|
Sign up to set email alerts
|

Durable Mesenchymal Stem Cell Labelling by Using Polyhedral Superparamagnetic Iron Oxide Nanoparticles

Abstract: Small polyhedral superparamagnetic iron oxide (SPIO) nanoparticles (<10 nm) coated with a thin layer of silica were prepared (SPIO@SiO(2) and SPIO@SiO(2)-NH(2)). Surface modification of the small polyhedral silica-coated SPIO nanoparticles with amines led to substantially higher mesenchymal stem cell (MSC) labelling efficiency without the use of additional transfecting agents. Therefore, amine surface-modified nanoparticles (SPIO@ SiO(2)-NH(2)) appeared to be the preferred candidate for MSC labelling. In vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 51 publications
6
58
0
Order By: Relevance
“…Among them, APTES is one of the most frequently used to produce the aminosilane (SiO 2 -NH 2 ) coating to enhance protein and cell adhesion. 27,28 SiO 2 -NH 2 -coated SPIO (SPIO@SiO 2 -NH 2 ) nanoparticles prepared by alkaline hydrolysis of APTES have been reported by the present authors 29 and other groups. [30][31][32] In a previous study, SPIO@SiO 2 -NH 2 nanoparticles were applied to rabbit mesenchymal stem cell (MSC) labeling.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Among them, APTES is one of the most frequently used to produce the aminosilane (SiO 2 -NH 2 ) coating to enhance protein and cell adhesion. 27,28 SiO 2 -NH 2 -coated SPIO (SPIO@SiO 2 -NH 2 ) nanoparticles prepared by alkaline hydrolysis of APTES have been reported by the present authors 29 and other groups. [30][31][32] In a previous study, SPIO@SiO 2 -NH 2 nanoparticles were applied to rabbit mesenchymal stem cell (MSC) labeling.…”
Section: Introductionsupporting
confidence: 61%
“…[30][31][32] In a previous study, SPIO@SiO 2 -NH 2 nanoparticles were applied to rabbit mesenchymal stem cell (MSC) labeling. 29 It was shown that SPIO@ SiO 2 -NH 2 nanoparticles had a higher labeling efficiency than SiO 2 -coated SPIO (SPIO@SiO 2 ) nanoparticles. However, whether SPIO@SiO 2 -NH 2 nanoparticles offer a universally higher internalization efficiency than other surface coatings in different mammalian cell lines remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are thousands more in "pending" status. The imaging agents in MICAD encompass radioactive labeled small molecules [15], nanoparticles [16], proteins such as antibodies [36] and fluorescent tagged proteins [18], and labeled cells such as stem cells for tracking homing to tumors [19]. Moreover, there are 170 diverse biological applications corresponding to the imaging agents, ranging from biological transporter imaging, cell tracking, angiogenesis imaging to drug resistance and disease detection [20].…”
Section: Biomedical Imaging Researchmentioning
confidence: 99%
“…Tools have become available for handling the complexity of genotype [8][9][10][11][12], and similar advancements are needed to describe phenotype, especially as derived from imaging [4,[13][14][15][16][17][18][19][20]. Publicly accessible resources that support large image archives support file sharing and have so far not yet merged into a framework that supports the collaborative work needed to meet the potential of quantitative image analysis.…”
Section: Introductionmentioning
confidence: 99%
“…On the information side, various databases store information on ex vivo biomarkers (e.g., Early Detection Research Network Biomarker Database [8], Infectious Disease Biomarker Database) [9]. However, information resources for in vivo biomarkers, specifically quantitative imaging biomarkers, are notably lacking [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%